GERD-A Life Style Disorder, Managed and Treated By Homoeopathy - Dr. Deepak Sharma; Dr. Sachin Pal Singh; Dr. Sunil Kumar (Revista Electronica de Veterinaria, 2024)
Gastroesophageal reflux disease (GERD) is a common clinical problem, affecting many peoples worldwide. Gastro-esophageal reflux disease (GERD) occurs when stomach acid repeatedly flows back into the tube connecting your mouth and stomach (Esophagus). This Backward Acid reflux can irritate the lining of your Esophagus. Homeopathic Medicines Play a very beneficial role in treating and managing those types of problems without compromising on the patient’s wellness.